Analysis of The Quality of Plastic Sack Products using the Statistical Quality Control (SQC) Method - Rizquina Aldila Putri; Donoriyanto, Dwi Sukma (AI Society & STMIK Indonesia, 2024)
PT. XYZ is a PT work unit manufacturing company. Perkebunan Nusantara I Regional 4 is engaged in the plastic sack industry which produces 2 products, namely outer bags and inner bags. The research carried out aims to determine and measure the level of product quality and provide appropriate product improvement suggestions for quality control problems in plastic sack products in PT. XYZ. The method used is Statistical Quality Control (SQC). Based on the results of research on Statistical Quality Control (SQC), there are 5 production stations and there are each type of defect at each production station. The defects that affect product quality are 14,541 kg of holey film defects, 13,849 kg of uneven threads, 22,706 kg of outgoing threads, 17,876 kg of jagged webbing, 10,186 kg of misprinting, 8,846 kg of faded colors, 11,323 kg of inner holes. , and opened seal of 3,206 kg. There are suggestions for improvements that can be proposed for each defect by adjusting the factors in the fishbone diagram.